Growth and reproductive dynamics of the South American red shrimp, Pleoticus muelleri (Crustacea: Solenoceridae), from the southeastern coast of Brazil - Castilho, A. L. [UNESP]; Wolf, M. R. [UNESP]; Simoes, S. M. [UNESP]; Bochini, G. L. [UNESP]; Fransozo, V.; Costa, Rogério Caetano da [UNESP] (Elsevier B.V., 2012)
The increase in the fishing fleet in southeastern Brazil and the decrease in the landings of profitable shrimp species have contributed to the incorporation of additional species into those fisheries, such as Pleoticus muelleri. The goal of the present study is to investigate the growth and reproductive dynamics of P. muelleri in the Southeastern coast of Brazil over a period of two years. Monthly collections were conducted in Ubatuba (UB) and Caraguatatuba (CA) using a commercial shrimp fishing boat equipped with "double-rig" nets. Each region was divided into 7 sampling stations up to 35 m deep. Population parameters from size frequency distributions (carapace length = CL), growth, longevity, sex ratio, and abundance of individuals in each life period (demographic class), from both sampling areas were analyzed and compared. The relationship between abiotic factors and abundance of each demographic class was assessed using a Canonical Correlation Analysis (CCorrA). A total of 19,816 individuals were collected, of which 5341 were measured, with an estimated longevity of 2.02 (UB) and 2.15 (CA) years for females and 1.80 (UB) and 1.96 (CA) years for males. There was a statistically significant bias in sex ratio toward females (Chi-square test, p<0.05) in both regions. The CCorrA resulted in a canonical correlation coefficient of 0.32 (p<0.00001). Both temperature and grain size composition of the sediment showed high correlation mainly with the presence of reproductive females, followed spermatophore-bearing males and recruits. In general, these demographic classes were most common in conditions of low temperature and fine sediments. These findings, as well as other studies carried out in colder regions with the same species, are consistent with the classical paradigm of lower longevity at lower latitudes. However, our results also suggest that this species maintained abiotic preference as populations located in cold temperate regions, mainly with temperature, indicating a different behavior from other shrimp species explored by fishery in the same region. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: Reproduction; Habitat selection; Longevity; Latitudinal variation